Genetic Contribution to the Pathogenesis of Primary Biliary Cholangitis - Satoru Joshita; Takeji Umemura; Eiji Tanaka; Masao Ota (Journal of Immunology Research)
Formerly termed primary biliary cirrhosis, primary biliary cholangitis (PBC) is a chronic and progressive cholestatic liver disease characterized by the presence of antimitochondrial antibodies. Ursodeoxycholic acid (UDCA) therapy is the most effective and approved treatment for PBC and leads to a favorable outcome in the vast majority of cases. Although the etiology of PBC has not yet been elucidated, human leukocyte antigen (HLA) class II alleles have been consistently associated with disease onset for decades. Individuals in different geographic regions of the world may have varying susceptibility alleles that reflect indigenous triggering antigens. In this review, we describe the influence of HLA alleles and other gene polymorphisms on PBC along with the results of genome-wide association studies (GWAS) on this disease.